Analyzing Multimodal Text Use in Teaching Vocabulary: A Qualitative Study at SMPN 40 Medan - Nursella Subadar; Israya Oktaviana Sinaga; Dessy Natalia Sinaga; Dolli Rotua Sinaga; Jonris Tampubolon (English Lecturers and Teachers Association (ELTA), 2026)
This study investigates the use of multimodal texts in teaching English vocabulary at SMPN 40 Medan, focusing on how teachers integrate multimodal resources, how students perceive these practices, and which types of multimodal texts are considered most helpful. Grounded in theories of multimodality and multimedia learning, the study addresses a gap in Indonesian junior high school contexts where vocabulary instruction often remains textbook-centered despite curriculum encouragement for digital literacy and student-centered learning. This study contributes to the limited empirical research on multimodal vocabulary instruction in Indonesian junior high school contexts. Using a qualitative descriptive design, the research draws on classroom observation, semi-structured interviews, and analysis of instructional materials to triangulate findings. The analysis shows that multimodal texts, particularly digital slides that combine text and visuals, support vocabulary learning by increasing engagement, clarifying meaning, and strengthening retention. Interactive quizzes enhance motivation and opportunities for review, while short audio and video materials support pronunciation and contextual understanding when guided through pausing and focused tasks. However, implementation is shaped by unstable internet access, limited devices, and the need for occasional translation support. Overall, the study highlights that multimodal vocabulary instruction is most effective when teachers connect visual, audio, and video input with meaningful practice and reinforcement while adapting to technological constraints. Keywords : Multimodal texts; vocabulary acquisition; EFL instruction